2009
DOI: 10.1590/s1413-41522009000100001
|View full text |Cite
|
Sign up to set email alerts
|

Descoloração de efluentes aquosos sintéticos e têxtil contendo corantes índigo e azo via processos Fenton e foto-assistidos (UV e UV/H2O2)

Abstract: ResumoNo presente trabalho, processos de oxidação avançada, Fe 2+ /H 2 O 2 e UV/H 2 O 2 , e de fotólise (UV) foram empregados na descoloração de dois efluentes sintéticos, contendo corantes tipo índigo e azo, e de um efluente de lavanderia industrial. Experimentalmente, soluções em concentração de 20 mg/L dos corantes índigo carmim e vermelho congo, respectivamente 43 µmol/L e 29 µmol/L, e o efluente têxtil (pH = 3) foram submetidos a diferentes condições oxidantes sob temperatura ambiente (27 ºC). As remoções… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 25 publications
2
6
0
7
Order By: Relevance
“…These results show that, among the studied AOPs, photolysis was more efficient to oxidixe RhB in aqueous solution, while it took the Fenton reaction 30 min to reach the same efficiency. Works conducted by Amorim et al (2009) and Salgado et al (2009) show that photolysis reactions showed better results for the discoloration of the dyes reactive red 195 and indigo carmine (100 % dicoloration in 1 min), respectively, when compared with homogeneous Fenton reactions, which corroborates the results obtained in this study. Salgado et al (2009) show that the discoloration of indigo carmine by the Fenton reaction also yielded excellent results, decoloring 100 % of the dye in 3 min.…”
Section: Methodssupporting
confidence: 89%
See 3 more Smart Citations
“…These results show that, among the studied AOPs, photolysis was more efficient to oxidixe RhB in aqueous solution, while it took the Fenton reaction 30 min to reach the same efficiency. Works conducted by Amorim et al (2009) and Salgado et al (2009) show that photolysis reactions showed better results for the discoloration of the dyes reactive red 195 and indigo carmine (100 % dicoloration in 1 min), respectively, when compared with homogeneous Fenton reactions, which corroborates the results obtained in this study. Salgado et al (2009) show that the discoloration of indigo carmine by the Fenton reaction also yielded excellent results, decoloring 100 % of the dye in 3 min.…”
Section: Methodssupporting
confidence: 89%
“…Works conducted by Amorim et al (2009) and Salgado et al (2009) show that photolysis reactions showed better results for the discoloration of the dyes reactive red 195 and indigo carmine (100 % dicoloration in 1 min), respectively, when compared with homogeneous Fenton reactions, which corroborates the results obtained in this study. Salgado et al (2009) show that the discoloration of indigo carmine by the Fenton reaction also yielded excellent results, decoloring 100 % of the dye in 3 min. In the same study, the discoloration of 100 % congo red occurred at 5 and 1 min, when photolysis and Fenton reactions were performed, respectively.…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…A planta é ainda rica em rotenóides que apresentam ação inseticida (Kamal & Mangla, 1993 tornar amareladas e prejudicar a produção de pigmento (Sandberg, p. 27, 1989 (Quintero & Cardona, 2010). As substâncias corantes e outros subprodutos, contidos nesses efluentes, contribuem significativamente para a poluição de recursos hídricos, já que dificultam a penetração de raios solares afetando diretamente os produtores primários, que são a base da cadeia alimentar de rios e mares, prejudicando a fauna e a flora; além disso, são substâncias carcinogênicas e mutagênicas (Salgado et al 2009). Os tecidos tingidos com índigo sintético são responsáveis por grande parte da demanda mundial, sendo que esse pigmento, particularmente é extremamente tóxico e, em humanos, pode causar irritações de pele e de olhos (Quintero & Cardona, 2010).…”
Section: Plantas Tintoriais E Técnicas De Extraçãounclassified